Growth performance and intestinal morphology of broilers fed low protein and low methionine diets supplemented with putrescine - Hashemi, Seyed Mohammad (2013)
Polyamines (PA) including putrescine (PUT), spermidine(SPD), and spermine (SPM) are a subgroup of biogenic amines and biosynthesized through ornithine decarboxylation. They are completely protonated at physiologic pH and this electrical property of PA enables them to bind with negatively charged macromolecules such as proteins and nucleic acids and to accomplish a range of particular roles that make them indispensable for growth and cell proliferation. The effects of polyamines on protein synthesis are exerted through their impact on transcription of more than 300 kinds of RNA. Moreover, the calcium-sensing receptor which regulates calcium homeostasis and release of parathyroid hormone can be activated by calcium ions and PA. High levels of dietary PA are reported to be toxic but lower level is strongly needed by the animals and plants. Fast growing tissues, like intestinal mucosa, are in high need of PA. Body requirement of PA is provided by dietary source, intestinal microbes and endogenous biosynthesis. Long term feeding of polyamine deficient diets would be resulted in a significant hypoplasia of the small intestinal and colonic mucosa. Luminal PA is important local factors for growth and the development of small intestinal and colonic mucosa. The influence of dietary PA on performance and nutrient digestibility in poultry nutrition is poorly investigated. So, the current study aimed to investigate the effects of dietary supplemental PUT on broiler growth performance, nutrient digestibility and intestinal morphology with protein-deficient and Met-deficient diets. Moreover, it is to be investigated that whether microbial metabolite, produced by lactobacillus, is effective on luminal polyamine content or not. In the 1st experiment different dietary levels of PUT (0, 0.01, 0.02, 0.03, 0.04 & 0.05 %) considered as treatments in young broilers. Results indicated that 0.01, 0.02, 0.03 and 0.05% PUT added to the diet caused significantly (P<0.05) increase in body weight gain (BWG) in 21 day old chicks. In 14 days old chicks 0.04% PUT affected crude protein (CP) digestibility adversely, but in older age (21 days), this effect was not observed. This suggested a relationship between the age and dietary PUT effects. Dietary PUT increased intestinal villus height (VH) and crypt depth (CD). None of the blood parameters including cholesterol, triglyceride, glucose, calcium and phosphorus were influenced by levels of dietary PUT. In the 2nd experiment the effects of added dietary PUT and protein deficient diet was investigated. Low CP decreased body weight gain (BWG) and improved protein efficiency ratio (PER) significantly (P< 0.05). Added PUT did not change BW of the chicks at any levels of CP. PUT improved the energy efficiency ratio (EER), showing that PUT is involved in energy metabolism. Low CP diet cause higher Ca digestibility and lower dry matter (DM) digestibility and intestinal VH. Tibia calcium content and pancreas weight are negatively affected by PUT in 21 days old birds. We observed that intestine and liver PA content is not influenced by dietary CP and PUT. According to the results of this study age is strongly affecting intestine and liver PA. In the third experiment methionine (Met) deficient diet and dietary PUT supplementation considered as treatments. Met deficiency diminished BWG, particularly in younger age and affects whole period performance. Significant BWG depletion was observed in PUT supplemented birds due to Met deficiency. Nutrients digestibility, VH and CD were not affected by Met and PUT levels in this trial. PUT is beneficial for tibia Ca level, especially at younger ages (10 days) but in older age (21 days) dietary PUT was harmful on tibia Ca content. Blood cholesterol, triglyceride and glucose were not affected by dietary Met and PUT level. The dietary Met level used in the current study had no effects on humoral immune response. However, PUT increased antibody production of challenged chicks against IBD. Furthermore, it was concluded that, the broiler chicken at older age when metabolism rate is high; require more PA because the PA content of the small intestine increases at older age. Dietary Met and PUT are not affecting intestinal tissue PA content as well as liver. Finally, in the fourth experiment the effects of microbial liquid metabolite (LM) produced by single strain of L. plantarum and dietary PUT on broiler performance and luminal PA was studied. LM had no influence on broiler performance that could be due to single strain metabolite. However, 0.05% dietary PUT adversely affected on BWG and protein efficiency ratio (PER) in the starter period (0-21 days). In current study, nutrient digestibility was also not affected by PUT and LM. Interaction between LM and PUT increased duodenal VH. LM had no effect on blood cholesterol, triglyceride and glucose. However, PUT increased blood glucose in 33 days old chicks.. The blood calcium increased clearly by interaction between LM and 0.03% dietary PUT. Based on the current findings, LM is capable of decreasing duodenal SPM and SPD. We found that LM and dietary PUT are not affecting PA content of ileal digesta and faeces. In conclusion, low dietary PUT (0.03%) may improve broiler BWG in the starter period and high level of dietary PUT (0.05%) have a negative effects on performance. The energy efficiency ratio of the chicks fed low-protein diets, is increased by PUT supplementation. Met deficiency in PUT supplemented group results poorer BWG. According to the current study, lactobacillus specious used, did not change intestinal luminal PA content. Polyamine content of Intestinal mucosa and liver tissue are not affected by dietary PUT and CP and Met deficiency, meaning that tissue polyamine metabolism is highly regulated